Modification des prédicats d’achèvements par les compléments de manière - Dejan Stosic (Studii de Lingvistica)
This paper reports on an empirical study of the interaction of the semantic notion of “manner” with the category of “lexical aspect” (or Aktionsart). Based on a sample of 4,000 sentences excerpted from Le Clézio’s novel Étoile errante, a detailed analysis of the combinatorics of verbal predicates and manner adjuncts has been carried out in order to verify whether and to what extent the four Vendlerian classes (States, Activities, Accomplishments and Achievements) are compatible with a syntagmatic specification of manner. The results are in line with Moline’s (2010) findings: all four types of situations are suited to modification by manner. While predicates describing Activities are the best candidates for modification by manner adjuncts, Achievements come second. This finding, which cannot be predicted from the literature, is the subject of a special development aimed at uncovering the nature of the qualitative specifications that these dynamic but fundamentally punctual situations can concede.